2019
DOI: 10.3390/jcm8040474
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Functional Changes of the Retina and the Choroid after Resolved Chronic CSCR

Abstract: Background: To investigate anatomical/functional changes after oral eplerenone therapy for chronic central serous chorioretinopathy (CCSC) in successfully treated eyes and fellow eyes and assess timing of foveal subretinal fluid (SRF) resolution. Methods: Twenty-one eyes of 21 patients suffering from CCSC with monolateral foveal SRF successfully treated with oral eplerenone were enrolled in this retrospective study (group 1). The fellow eyes (21 eyes; group 2), healthy or affected by CCSC, without foveal SRF w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Choroidal vasculature alterations are rarely reported in the literature after other treatments in CCSCR. Toto et al did not find any changes in retinal capillary plexuses or choroidal vasculature after eplerenone treatment of CSCR [46]. Fujita et al presented a small series of 6 patients in whom OCTA revealed choriocapillaries recovery after half-dose PDT treatment (improvement of flow signal) [47].…”
Section: Discussionmentioning
confidence: 99%
“…Choroidal vasculature alterations are rarely reported in the literature after other treatments in CCSCR. Toto et al did not find any changes in retinal capillary plexuses or choroidal vasculature after eplerenone treatment of CSCR [46]. Fujita et al presented a small series of 6 patients in whom OCTA revealed choriocapillaries recovery after half-dose PDT treatment (improvement of flow signal) [47].…”
Section: Discussionmentioning
confidence: 99%
“…In the latter study cohort, the mean time to complete foveal SRF resolution was 10.5 ± 8.0 months after treatment initiation and, at 24 months, foveal SRF resolution was achieved in 13 eyes (81%). Toto and colleagues [21] also demonstrated that eplerenone is effective in improving visual function and morphological parameters in eyes with chronic CSC. In their study cohort, a percentage of 71.4% of eyes had resolution of SRF within 2 months, while the remaining 28.6% had resolution at the 2-month follow-up visit.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as choroidal hyperpermeability have been described to explain this process [ 13 ]. In addition, leakage sites have been captured by various choroidal imaging techniques like fluorescein angiography (FA) and indocyanine green angiography (ICGA) to facilitate diagnosis ( Figure 1 ) [ 14 ]. These imaging methods are described in detail below.…”
Section: Introductionmentioning
confidence: 99%